2022
DOI: 10.3390/app12178438
|View full text |Cite
|
Sign up to set email alerts
|

Switching Learning Methods during the Pandemic: A Quasi-Experimental Study on a Master Course

Abstract: The COVID-19 pandemic marked an important breakthrough in human progress: from working habits to social life, the world population’s behaviours changed according to the new lifestyle requirements. In this changing environment, university courses and learning methods evolved along with other “remote” working activities. For this quasi-experimental study, we discuss the effectiveness of the changes made by the LUMSA University in Rome, comparing two different groups of students who attended a master’s course wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…The results of the present study are further strengthened with findings from an earlier study, which showed that all the changes made during the COVID-19 pandemic showed learning effectiveness [ 3 ]. Another study showed that the network scale of most courses did not change significantly, giving evidence that the COVID-19 pandemic did not notably change the scale of course interaction [ 45 ].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The results of the present study are further strengthened with findings from an earlier study, which showed that all the changes made during the COVID-19 pandemic showed learning effectiveness [ 3 ]. Another study showed that the network scale of most courses did not change significantly, giving evidence that the COVID-19 pandemic did not notably change the scale of course interaction [ 45 ].…”
Section: Discussionsupporting
confidence: 87%
“…Under such conditions, universities across the globe were affected by the pandemic and the sudden transition from face-to-face to online teaching. University curricula and teaching techniques changed along with other “remote” professional activities in this shifting environment [ 3 ]. Research studies have highlighted several opportunities for the development of distance education and the technical readiness for such during the COVID-19 pandemic [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…AI-powered solutions that provide teachers with insights into how students respond to learning content and style can assist create a more dedicated learning environment for students from different backgrounds [24]. Additionally, AI-based learning can be modified to develop the skills that companies need in students, including those from different countries [25]. Chatbots for learning and research, adaptive assessment, predictive analytics, and customized learning experiences are a few examples of specialized AI applications in education.…”
Section: 1mentioning
confidence: 99%
“…AI-powered tools can provide instructors with insights into how students respond to learning content and style, creating a more dedicated learning atmosphere for international students from diverse backgrounds. Additionally, AI-based learning can be tailored to develop the skills and abilities employers seek in learners, including those from different countries [20]. Specific examples of AI applications in education, such as personalized learning experiences, adaptive testing, predictive analytics, and chatbots for learning and research, will be examined in this section for their potential impact on international students.…”
Section: Current Applications Of Ai In Educationmentioning
confidence: 99%